Dialogue as a Response to the Psychiatrization of Society? Potentials of the Open Dialogue Approach - von Peter, Sebastian; Bergstrøm, Tomi; Nenoff-Herchenbach, Irene; Hopfenbeck, Mark Steven; Pocobello, Raffaella; Aderhold, Volkmar; Alvarez-Monjaras, Mauricio; Seikkula, Jaakko; Heumann, Kolja (Frontiers in Sociology, 2021)
In recent decades, the use of psychosocial and psychiatric care systems has increased world-wide. A recent article proposed the concept of psychiatrization as an explanatory framework, describing multiple processes responsible for the spread of psychiatric concepts and forms of treatment. This article aims to explore the potentials of the Open Dialogue (OD) approach for engaging in less psychiatrizing forms of psychosocial support. While OD may not be an all-encompassing solution to de-psychiatrization, this paper refers to previous research showing that OD has the potential to (1) limit the use of neuroleptics, (2) reduce the incidences of men-tal health problems, and (3) decrease the use of psychiatric services. It substantiates these po-tentials to de-psychiatrize psychosocial support by exploring the OD’s internal logic, its use of language, its processes of meaning-making, its notion of professionalism, its promotion of dia-logue, and how OD is set up structurally. The conclusion touches upon the dangers of co-optation, formalization, and universalization of the OD approach and stresses the need for more societal, layperson competencies in dealing with psychosocial crises.